500W circular coil parameters mathematical design for wireless power transfer with ferrite core - Nanda, Nadia Nazieha; Yusoff, Siti Hajar; Midi, Nur Shahida; Badawi, Ahmed Samir Abed (International Association of Online Engineering, 2022)
The efficiency of wireless pad designs with ferrite cores has been established in several investigations. However, they seldom offered a viable solution to the problem of modifying the ferrite form's geometric shape. The use of a ferrite core in the primary and secondary coils has been suggested by several researchers. The ferrite core design, on the other hand, is still in the works. Using the wrong ferrite core design might result in unnecessary extra weight and higher production costs. The circular coil design in the primary and secondary for wireless power transfer (WPT) in electric vehicles is studied in this research. The suggested coil design is used to develop mathematical design utilizing numerical solutions. Later, using Multisims software, this coil design is produced in simulation. The suggested coil design's power efficiency is examined and contrasted between computed and simulated results. Finally, based on the results of the power efficiency, a definitive discussion is presented.